Ultra-wideband reflective polarization converter based on anisotropic metasurface - 吴家梁 林宝勤 达新宇 (Chinese physics B, 2016)
In this paper, we propose an ultra-wideband reflective linear cross-polarization converter based on anisotropic metasurface. Its unit cell is composed of a square-shaped resonator with intersectant diagonal and metallic ground sheet separated by dielectric substrate. Simulated results show that the converter can generate resonances at four frequencies under normal incident electromagnetic（EM） wave, leading to the bandwidth expansion of cross-polarization reflection. For verification,the designed polarization converter is fabricated and measured. The measured and simulated results agree well with each other, showing that the fabricated converter can convert x- or y-polarized incident wave into its cross polarized wave in a frequency range from 7.57 GHz to 20.46 GHz with a relative bandwidth of 91.2%, and the polarization conversion efficiency is greater than 90%. The proposed polarization converter has a simple geometry but an ultra wideband compared with the published designs, and hence possesses potential applications in novel polarization-control devices.